APPLYING THE QUALITY MANAGEMENT SYSTEM AND OPTIMIZING ITS COSTS - Andrei DIAMANDESCU (Challenges of the Knowledge Society)
The approach of this paper is to optimize the costs of applying the integrated quality management systems in industrial organizations. In this case, the optimization implies the determination of the limit of the costs generated by the quality system to which a maximum benefit is obtained or, in other words, the minimum cost to which the company's activities may materialize in the expected results through the implementation of the quality management system. The cost optimization for quality can be achieved in a complex way that is less used in the practice of organizations by mathematical modeling, or by an easier way – the preferred method by the practitioners – by comparing the performance of the organization with a reference standard (e.g. ISO 9001 ), which captures the difference from performance prior to the implementation of the quality management system. To justify the application of the second way (through comparisons), we propose to present the results of the study conducted by several industrial enterprises in Romania that have implemented the integrated quality management system.